PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP PENINGKATAN DISIPLIN KINERJA GURU DI SMP AL KHER BEJI - Nizammuddin, Muhammad Rafly Syahlan; Hazin, Mufarrihul; Nursalim, Mochamad (Department of Islamic Education Management, 2025)
This study aims to analyze the influence of principal leadership and organizational culture on teacher performance discipline at SMP Al Kher Beji. This study uses a quantitative approach with a descriptive correlational method. Data were collected through questionnaires distributed to 14 respondents consisting of permanent teachers, non-permanent teachers, and principals. The variables studied include principal leadership, organizational culture, and teacher performance discipline. Data analysis was carried out using SPSS software version 20, including validity, reliability, Pearson correlation, and multiple regression tests. The results showed that principal leadership has a significant influence on teacher performance discipline with dimensions such as intellectual stimulation, inspirational motivation, individual consideration, and ideal influence. In addition, organizational culture based on Islamic boarding school values ​​such as amanah, ihsan, and ta'awun also plays an important role in building teacher discipline. Multiple regression analysis shows that principal leadership and organizational culture simultaneously influence teacher performance discipline with a determination coefficient of ?2 of 65%, which means that 65% of the variation in teacher work discipline can be explained by these two variables. Principal leadership and organizational culture significantly influence the improvement of teacher performance discipline. The combination of effective leadership and the implementation of a strong organizational culture creates a conducive work environment, increasing teacher responsibility and discipline.